Planning of clean water distribution network Kamosope Village, Pasir Putih District, Muna Regency. Issue 1 (October 2021) - Sriyani, R; Putri, T S; Rachman, R M; Takdir,
Abstract: The availability of clean water is essential for human life because clean water is the primary human need. It is imperative to plan a clean water supply system that is appropriately managed. Kamosope Village does not yet have a reasonable and adequate clean water network system, so it is necessary to plan a sound clean water supply network system to serve the community. The source of water to be used is river water. The designed clean water network system collects water from the river then the water is distributed to the population through a gravity system. The clean water network system is planned to meet the needs of clean water until 2029. The need for clean water is calculated based on the projected population using the Least Square method. From the calculation results, the need for clean water in Kamosope Village in 2029, with 723 people, reaches 1.753 liters/second. Kamosope river discharge based on field measurements using the buoy method is 0.535 m³/second or 107 liters/second. Distribution pipe diameters are the inch, 1 inch, 1½ inch, and 2 inches. EPANET 2.0 software is used to design the clean water network system.